RNA m6A methylation regulates virus–host interaction and EBNA2 expression during Epstein–Barr virus infection. Issue 2 (12th January 2021) - Zheng, Xiang; Wang, Jia; Zhang, Xiaoyue; Fu, Yuxin; Peng, Qiu; Lu, Jianhong; Wei, Lingyu; Li, Zhengshuo; Liu, Can; Wu, Yangge; Yan, Qun; Ma, Jian
Abstract: Introduction: N 6 ‐methyladenosine (m 6 A) is the most prevalent modification that occurs in messenger RNA (mRNA), affecting mRNA splicing, translation, and stability. This modification is reversible, and its related biological functions are mediated by "writers, " "erasers, " and "readers." The field of viral epitranscriptomics and the role of m 6 A modification in virus–host interaction have attracted much attention recently. When Epstein–Barr virus (EBV) infects a human B lymphocyte, it goes through three phases: the pre‐latent phase, latent phase, and lytic phase. Little is known about the viral and cellular m 6 A epitranscriptomes in EBV infection, especially in the pre‐latent phase during de novo infection. Methods: Methylated RNA immunoprecipitation sequencing (MeRIP‐seq) and MeRIP‐RT‐qPCR were used to determine the m 6 A‐modified transcripts during de novo EBV infection. RIP assay was used to confirm the binding of EBNA2 and m 6 A readers. Quantitative reverse‐transcription polymerase chain reaction (RT‐qPCR) and Western blot analysis were performed to test the effect of m 6 A on the host and viral gene expression. Results: Here, we provided mechanistic insights by examining the viral and cellular m 6 A epitranscriptomes during de novo EBV infection, which is in the pre‐latent phase. EBV EBNA2 and BHRF1 were highly m 6 A‐modified upon EBV infection. Knockdown of METTL3 (a "writer") decreased EBNA2 expression levels. The emergent m 6 A modifications induced by EBV infection preferentially distributed in 3ʹ untranslated regions of cellular transcripts, while the lost m 6 A modifications induced by EBV infection preferentially distributed in coding sequence regions of mRNAs. EBV infection could influence the host cellular m 6 A epitranscriptome. Conclusions: These results reveal the critical role of m 6 A modification in the process of de novo EBV infection. Abstract : The viral and cellular N 6 ‐methyladenosine (m 6 A) epitranscriptomes were changed during de novo Epstein–Barr (EBV) infection in B cells. EBV EBNA2 was a significant m 6 A‐modified viral transcript, and cellular TLR9 and FAS genes' m 6 A modification levels are also modulated by EBV infection.